Thromboangiitis obliterans (Buerger's disease) - Rivera-Chavarría, Ignacio J. (Ann Med Surg (Lond), 2016)
Thromboangiitis Obliterans is a non-atherosclerotic inflammatory disease of unknown etiology, which has a strong association with tobacco. We present current concepts on the pathophysiology and diagnosis, as well as a review in treatments.